Exercise as part of a cystic fibrosis therapeutic routine. (June 2012) - Rand, Sarah; Prasad, S Ammani
The role of exercise in cystic fibrosis (CF) is well established, and over the last three decades it has become an important component in the management of all individuals with CF. The role of exercise as a prognostic indicator or therapeutic tool is an important area of research interest in CF care internationally. This article summarizes the currently available evidence regarding exercise capacity in CF, the potential effects of exercise on health outcomes in CF and the challenges faced when trying to incorporate exercise into a CF therapeutic routine, and highlights some methods to facilitate the incorporation of exercise into CF therapeutic routines.